Incorporating the dynamics of leverage into default prediction - Gunter Löffler; Alina Maurer (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
A firm's current leverage ratio is one of the core characteristics of credit quality used in statistical default prediction models. Based on the capital structure literature, which shows that leverage is mean-reverting to a target leverage, we forecast future leverage ratios and include them in the set of default risk drivers. The analysis is done with a discrete duration model. Out-of-sample analysis of default events two to five years ahead reveals that the discriminating power of the duration model increases substantially when leverage forecasts are included. We further document that credit ratings contain information beyond the one contained in standard variables but that this information is unrelated to forecasts of leverage ratios.
Keywords: G32; G33; 330; default prediction; discrete duration model; leverage targeting; mean reversion; credit rating; Kreditwürdigkeit; Kreditrisiko; Prognoseverfahren; Kapitalstruktur; Mean Reversion; Theorie